2004
DOI: 10.1111/j.1552-6569.2004.tb00277.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Brain Atrophy With Cognitive Dysfunction, Mood Disturbances, and Personality Disorder in Multiple Sclerosis

Abstract: Neuropsychological impairment is a common feature of multiple sclerosis. Affected patients often have deficits in information-processing speed and memory and exhibit psychopathological states such as depression. A minority of patients have rarer affect/mood disorders such as euphoria sclerotica and pathological laughter/crying. Neuropsychological impairment is a major predictor of low quality of life, unemployment, and caregiver distress. Studies evaluating correlations between neuropsychological impairment an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0
9

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(63 citation statements)
references
References 89 publications
3
51
0
9
Order By: Relevance
“…Several cross sectional studies demonstrated that the pathogenesis of CI in MS patients might not depend just on the extent and severity of the pathological process in the brain lesions, but also on the pathological changes affecting the normal appearing brain tissue [47-49]. Considering that, we could take into account the possible vascular hypothesis as a possible contribute to the presence of a spread or regional brain atrophy, which is one of the strongest factor correlated with the CI in MS [50-52]. Impaired cerebral perfusion seems to be related to CI [18] and a widespread cerebral hypo perfusion in MS, described as a potential cause of brain atrophy [50-52], could be the result of the venous outflow obstructions as seen in the CCSVI [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several cross sectional studies demonstrated that the pathogenesis of CI in MS patients might not depend just on the extent and severity of the pathological process in the brain lesions, but also on the pathological changes affecting the normal appearing brain tissue [47-49]. Considering that, we could take into account the possible vascular hypothesis as a possible contribute to the presence of a spread or regional brain atrophy, which is one of the strongest factor correlated with the CI in MS [50-52]. Impaired cerebral perfusion seems to be related to CI [18] and a widespread cerebral hypo perfusion in MS, described as a potential cause of brain atrophy [50-52], could be the result of the venous outflow obstructions as seen in the CCSVI [19].…”
Section: Discussionmentioning
confidence: 99%
“…Considering that, we could take into account the possible vascular hypothesis as a possible contribute to the presence of a spread or regional brain atrophy, which is one of the strongest factor correlated with the CI in MS [50-52]. Impaired cerebral perfusion seems to be related to CI [18] and a widespread cerebral hypo perfusion in MS, described as a potential cause of brain atrophy [50-52], could be the result of the venous outflow obstructions as seen in the CCSVI [19]. Although there is no strong evidence suggesting that CCSVI is a cause of MS, there is some evidence that a slower cerebral venous flow in patients with MS might be secondary to the reduced cerebral blood flow [19].…”
Section: Discussionmentioning
confidence: 99%
“…29,30 In a study that explored the relationship between five brain MRI indices of pathology (T1 and T2 lesion volume, third ventricle width, bicaudate ratio and brain parenchymal fraction) and a host of cognitive variables, it was third ventricle width that emerged as the most robust predictor of cognitive impairment. 31 Moreover, the strongest correlation was found with the SDMT. More recently, subtle indices of thalamic pathology, such as resting state functional connectivity 32 and altered diffusion tensor imaging metrics such as mean diffusivity 33 have been linked to impaired cognition in MS patients.…”
Section: Discussionmentioning
confidence: 94%
“…16,17 WBA can be detected at all stages of MS disease and represents a summation of the destructive pathologic processes in MS. Many studies show significant correlations between WBA and overall clinical disability, cognitive impairment, 1822 depression, 23 fatigue, 24,25 and quality of life. 26,27 However, WBA is a relatively crude measure of overall brain injury, lacking granularity to characterize localized injury.…”
Section: Introductionmentioning
confidence: 99%